The Relationship between Eye-Hand Coordination and Agility to the Dribble Ability of the U12 Basketball Player - Ervinanda, Winan Dita; Wicaksono, Anggit (Universitas Negeri Surabaya, 2024)
Purpose: This study examines the correlation between eye-hand coordination, agility, and dribbling skills in U12 Jaguar Pantherchildren. Materials and Methods: The study was a correlational investigation that included ten male participants under 12 and belonged to the Jaguar Panther group. The eye-hand coordination test (ball throw and catch test), agility test (T-run), and basketball dribbling test (Aahperd Basketball Control Dribble Test) were utilized to conduct the measurements. Result: The statistical analysis revealed that the relationship between eye-hand coordination and dribbling ability is significant at 0.063. Similarly, the relationship between agility and dribbling ability has a significance value of 0.173. Additionally, the relationship between eye-hand coordination, agility, and dribbling ability has a significance value of 0.057. Conclusion: All three significance values were greater than 0.05, indicating a lack of significant relationship between eye-hand coordination, agility, and dribbling ability in U12 Jaguar Panther children.